The Case of Ownership of the Lands of Kokkoz Valley (based on Archive Sources) - Eldar Vaniev (Крымское историческое обозрение)
On the example of covering a court dispute about the ownership of the largest land plot in the Crimea of the XIX century, the problem of the law enforcement in the field of land use in Taurida was raised. It points to such a feature of land use in Taurida province, as simultaneous functioning within the same territory of two land use systems: Islamic and continental. From a historical and legal point of view, the demand that arose is interesting in itself as a legal monument to complex land disputes in the Crimea in the XIX century.